Монгол Улс дахь Ислам: түүх, өнөөгийн байдал, хэтийн төлөв - М, Хурметхан (Journal of International Studies, 2013)
Тус өгүүлэлд Монгол Улс дахь исламын шашны түүх, өнөөгийн байдал, хэтийн төлвийн талаар тусган харуулжээ. Islam in Mongolia: past, present and future Mongolia is one of the countries where Islam has spread. Studying the history of spread of Islam and present situation in Mongolia which is a part of Central Asian civilization became an important issue. Islam and Muslims in Mongolia overcame difficult and harsh fate in various phases of history and reached the period of today’s democracy and globalization and favourable conditions of spread of Islam in Mongolia.